(untitled) (Orkopata. Revista de Lingüística, Literatura y Arte, 2025)
Teacher jargon has undergone transformations resulting from the technological mediation of educational processes. In this regard, this article aims to characterize the transformation of teachers’ jargon at Chiloé Educational Institution between 2020 and 2024, based on the technological mediation of teaching processes. The study employs a qualitative, descriptive, and interpretive methodology. The corpus consists of twenty primary school lessons (ten in-person and ten virtual) observed between 2020 and 2024. The data were analyzed according to four linguistic criteria: sociolinguistics (teacher jargon and languages in contact), semantics (neologisms and semantic shifts), pragmatics (recontextualization of expressions, presuppositions, and implicatures), and syntax (word order and non-conventional constructions). The results reveal a transformation of teacher jargon characterized by the incorporation of new technological terms, the reinterpretation of traditional pedagogical concepts, and the adaptation of communicative strategies to the interactive conditions of digital environments. Furthermore, the findings confirm a growing discursive hybridization between traditional pedagogical orality and new forms of communication mediated by technology. It is concluded that technological mediation has impacted teacher jargon through the emergence of neologisms, semantic changes, and discursive adaptations that reflect the transformation of pedagogical practices toward digital environments.